The significance of double mandibular osteotomy for surgical treatment of large aneurysm of internal carotid artery above mandibular angle. A case report and literature review. Issue 11 (23rd November 2022) - Tilaveridis, Ioannis; Tatsis, Dimitris; Venetis, Gregory; Trelopoulos, Georgios; Mylonas, Anastasios
Abstract: The aim of this study is to report a case of an unusual large aneurysm of the internal carotid approached with a doubly mandibular osteotomy in order to prove the significance and the excellent result of the specified surgical procedure because of the cooperation of maxillofacial and vascular surgeons. The double mandibular osteotomy is described, as well as the bypass of the aneurysm and the anastomosis of the peripheral edges of the artery. The double mandibular osteotomy can deliver the internal carotid artery from the bifurcation to its entrance to the skull base through the carotid canal and can offer the opportunity to the vascular surgeon to perform the anastomosis easily, quickly and safely.